Does Top Management Team Media Exposure Affect Corporate Social Responsibility? - Jiang, Yichi; Zhang, Liyuan; Tarbert, Heather (Frontiers in Psychology, 2022)
This study examines the impact of top management teams (TMTs) media exposure on corporate social responsibility (CSR) and the moderating effect of TMTs characteristics based on the upper echelons theory and stakeholder theory. From the observations of 5,352 firm-year observations between 2010 and 2019, multiple regression analysis is conducted to empirically test whether TMTs media exposure can promote CSR. TMTs media exposure is further divided into paper media, online media to reveal the impact of different types of TMTs media exposure on CSR. Some robustness tests are also conducted to strengthen the regression results. The results found that a high level of TMTs media exposure promotes social responsibility. The TMTs power and political connections negatively moderate the relationship between TMTs media exposure and CSR. The main contribution of this study is to develop a TMTs media exposure model to assess the impact of TMTs media exposure on CSR, providing a theoretical contribution to the existing literature and enriching the research in the CSR context from the perspective of the TMT characteristics moderating role.